Enhancement of gel characteristics of NaOH-induced duck egg white gel by adding Ca(OH)2 with/without heating. (June 2020) - Ai, Minmin; Zhou, Quan; Xiao, Nan; Guo, Shanguang; Cao, Yuanyuan; Fan, Hong; Ling, Ziting; Zhou, Ledan; Li, Shuchang; Long, Jiaoli; Jiang, Aimin
Abstract: Egg white protein (EWP) can form a gel under alkali condition, but there have been few reports on the gelling of EWP with the addition of Ca(OH)2 . In this paper, the effects of Ca(OH)2 and the heating process on the rheological, mechanical and microstructural properties, and intermolecular interactions of egg white gel (EWG) were investigated. Results suggested that the pH of EWG increased markedly upon addition of Ca(OH)2 but declined after heating, and the surface hydrophobicity of EWP decreased significantly due to the embedding and destruction of hydrophobic groups. And sulfhydryl groups and disulfide bonds contents decreased after heating. Secondary structural analysis showed that β-sheet content increased, and β-turn content decreased after the addition of Ca(OH)2, while heating decreased random structures and α-helical content and increased β-turn content. The results of electrophoresis revealed that the addition of Ca(OH)2 degraded protein patterns gradually, while heating destroyed EWP. Textural test results demonstrated the hardness value increased remarkably upon addition of Ca(OH)2 and heating, but springiness declined gradually. The addition of Ca(OH)2 improved storage (G′) and loss (G″) modulus of EWG, which might relate to the formation of calcium bridges and ion interactions. The surface morphology of EWG transformed from yellow to brown or red after heating. Rough and irregular microstructure formed when the amount of Ca(OH)2 increased, while the microstructure became more compact and regular after heating. These results suggested that addition of Ca(OH)2 significantly affected the represented characteristics of EWG, and heating changed the intermolecular interactions and physicochemical properties. Graphical abstract: Image 1 Highlights: Surface hydrophobicity was weakened after adding Ca(OH)2 and heating process. Heating process declined random structure, α-helical and increased β-turn content of EWP. The content of sulfhydryl groups and disulfide bonds reduced obviously after heating process. Adding Ca(OH)2 promoted the formation of gelation, resulting in the increase of G′ and G″.